Effectiveness of Activated Carbon from Jackfruit Skin for The Heavy Metal Lead (Pb) Adsorption Using The Langmuir and Freundlich Equations - Arke, Nadya Ramadhani; Sari, Dewa Ayu Made Dearwita; Dewati, Retno (Equilibrium Journal of Chemical Engineering, 2024)
Activated carbon is a commonly used medium for adsorption to combat environmental pollution in both water and air. It is produced from plant or plantation waste containing carbon. Jackfruit skin, often considered as plantation waste, contains lignocellulosic compounds and has the potential to be used as active carbon. Activated carbon from jackfruit skin has a good absorption capacity and can absorb heavy metal waste such as lead (Pb). A recent study aimed to evaluate the absorption effectiveness of active carbon from jackfruit skin. The process involved making activated carbon using the pyrolysis method, and then analyzing its lead absorption capacity in lead nitrate solution by varying the weight of the activated carbon (10g, 15g, 20g, 25g, 30g) and the adsorption time in minutes (40, 60, 80, 100, 120). The levels of absorbed lead on activated carbon were tested using Atomic Absorption Spectrophotometry (AAS) at a wavelength of 283.3 nm. The research findings indicate that the effectiveness of activated carbon absorption reaches 99%, and the appropriate equation model for the adsorption process is the Freundlich isotherm, indicating a multilayer adsorption process.Keywords:Adsorption Isotherm, Activated Carbon Jackfruit Skin, Lead (Pb)